Polymer nanoparticles with a sensitive CO2‐responsive hydrophilic/hydrophobic surface. Issue 21 (5th September 2019) - Shieh, Yeong‐Tarng; Tai, Pei‐Yu; Cheng, Chih‐Chia
ABSTRACT: Poly(methyl methacrylate) (PMMA) nanoparticles with a sensitive CO2 ‐responsive hydrophilic/hydrophobic surface that confers controlled dispersion and aggregation in water were prepared by emulsion polymerization at 50 °C under CO2 bubbling using amphiphilic diblock copolymers of 2‐dimethylaminoethyl methacrylate (DMAEMA) and N ‐isopropyl acrylamide (NIPAAm) as an emulsifier. The amphiphilicity of the hydrophobic–hydrophilic diblock copolymer at 50 °C was triggered by CO2 bubbling in water and enabled the copolymer to serve as an emulsifier. The resulting PMMA nanoparticles were spherical, approximately 100 nm in diameter and exhibited sensitive CO2 /N2 ‐responsive dispersion/aggregation in water. Using copolymers with a longer PNIPAAm block length as an emulsifier resulted in smaller particles. A higher concentration of copolymer emulsifier led to particles with a stickier surface. Given its simple preparation and reversible CO2 ‐triggered amphiphilic behavior, this newly developed block copolymer emulsifier offers a highly efficient route toward the fabrication of sensitive CO2 ‐stimuli responsive polymeric nanoparticle dispersions. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 2149–2156 Abstract : This paper describes the development of a new concept in fabrication of multiple stimuli‐responsive diblock copolymers (MSDPs) to confer amphiphilic functions in an aqueous environment through the combination of water‐soluble polymers and hydrophobic polymers. These MSDPs possess unique pH‐sensitive and carbon dioxide/nitrogen gas‐switchable abilities, providing a potential route towards the fabrication of sensitive gas‐stimuli‐responsive polymer nanoparticles with spherical structures in dispersion or aggregation in aqueous media.